Hakikat Ilmu dan Filsafat dalam Filsafat Ilmu - Wiwin Setio Wati; Ulyana Maulidiyah; I Ketut Mahardika; Suratno Suratno (Peneliti.net, 2023)
This paper will answer questions about the meaning of philosophy, science, philosophy of science. This paper is a quqlitqtive research that intends to construct meaning through selected literatures. The scope of philosophy extends from all that exist and may exist. In order to gain a comprehensive understanding the philosophy of science, it is necessary to trace the meaning of philosophy and science itself both etymlogically and terminologically. Etymologically science comes from Arabic ’alima’ which means knowledge and terminologically science means exact and organized knowledge. Etymologically, philosophy comes from the Greek word philoshopia which means love of wisdom. Philosophical terminology has many definitions according to the definition of the philosophers themselves. Aristotle defines philosophy as knowledge which includes truth which includes the sciences of metaphysics, logic, rhetoric, ethics, and aesthetics. So that the philosophy of science can be interpreted as a philosophy which has the truth about knowledge that is exact and organized. Science is the material object of the philosophy of science. Its scope includes the ontological basis, namely what is the true meaning of knowledge, the epistemological basis, namely how to obtain that knowledge, and the axiological basis, namely the benefits possessed by knowledge.